The potter's field - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael, 2021)
When a newly plowed field recently given to the Benedictine Abbey of Saint Peter and Saint Paul yields the body of a young woman, Brother Cadfael is quickly thrown into a delicate situation. The field was once owned by a local potter named Ruald, who had abandoned his beautiful wife, Generys, to take monastic vows. Generys was said to have gone away with a lover, but now it seems as if she had been murdered. With the arrival at the abbey of young Sulien Blount, a novice fleeing homeward from the civil war raging in East Anglia, the mysteries surrounding the corpse start to multiply.